Implementation of Classroom Management in Improving the Effectiveness of Islamic Religious Education Learning at Tiwikrama Computer Vocational School, Mamuju Regency - Hasram Efendi; Sabar Narimo; Muthoifin Muthoifin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The role of religion in individual life functions as a value system that contains certain norms. For Muslims, the religious education that is mandatory for them to follow is Islamic religious education. As for realizing this universal view, this study aims to explain the process of implementing Classroom Management in Improving the Effectiveness of Learning Religious Education Islam at the Tiwikrama Computer Vocational School, Mamuju Regency. The type of research used is qualitative research. Based on the results of this study, it shows that: The planning and organization carried out by the teacher in improving the learning quality of Islamic Religious Education subjects at Tiwikrama Computer Vocational School, Mamuju Regency can be seen from the lesson plan made by the teacher where the teacher makes Indicators of learning achievement, learning objectives, learning methods, learning media, learning resources and assessment. Class management carried out by the teacher in improving the quality of learning for the Islamic Religious Education subject at Tiwikrama Computer Vocational School, Mamuju Regency by always paying attention to the elements of effectiveness in learning, which includes: Learning Materials, Learning Atmosphere, Media and Learning Resources, Besides understanding the elements in the effectiveness of the learning, the teacher must also know what steps should be taken by the teacher in learning, so that it can run effectively as expected. Class evaluation or learning evaluation is carried out by teachers in improving the quality of learning in Islamic Religious Education subjects at the Tiwikrama Computer Vocational School, Mamuju Regency where learning evaluation activities are carried out through several stages of activity, including: planning, implementation, monitoring, data processing and use of evaluation results.